NEGATIVE INFLUENCE OF DYNAMIC ENVIRONMENT ON PROGRAMS DIGITALIZATION OF MILITARY EDUCATION - Кубявка, Л.Б.; Шевченко, А.М.; Кубявка, М.Б. (Військовий інститут Київського національного університету імені Тараса Шевченка, 2023)
The negative effects of the dynamic environment on digitalization programs of military education have been studied. Specific features are highlighted and the influence of the dynamic environment on the characteristics of digitization projects and programs is considered. The results of such influences are characterized. Conceptual space for formal management of impacts on programs of digitalization of military education is formulated. The effects of the dynamic environment on the characteristics of digitization programs are considered. The results of such influences are highlighted. A mathematical model of the space of influences, an objective function, constraints and a decisive rule for determining management actions to counteract the influences that lead to negative consequences in digitalization programs are proposed. It is proposed to use the mathematical apparatus of the theory of non-force interaction as a scientific and methodological basis for finding the optimal solution for minimizing the costs of eliminating the consequences of negative impacts. The structure, list, subordination and distribution of obligations in the process of implementation of the programs of the digitalization of military education depend on the sources of influence characteristic of the dynamic environment, which lead to deviations, and determine the possibility of implementing the projects of these programs. Since the number of such sources in digitalization programs is significant, it is necessary to implement a systematic approach to the construction of management systems for digitalization programs of military education (MSDP ME), which will be effective in the conditions of Ukraine. And for this, it is necessary to develop methods and ways of managing the organizational and functional structure of higher education institutions, as well as the technologies of preparation, planning, and budgeting, which are the basis of building management systems in the conditions of numerous influences that arise during the implementation of digitalization programs. This article is devoted to solving this scientific problem. Therefore, the purpose of the work is to study the effects of the dynamic environment on the digitalization programs of higher educational institutions and the digitalization of military education, and to build a mathematical model of such effects, which can form the basis of the methodology for managing effects on projects and programs.

Досліджені негативні впливи динамічного оточення на програми цифровізації військової освіти. Виділені особливості та розглянуто впливи динамічного оточення на характеристики проєктів та програм цифровізації. Охарактеризовані результати таких впливів. Сформульовано понятійний простір для формального управління впливами на програми цифровізації військової освіти. Розглянуто впливи динамічного оточення на характеристики програм цифровізації. Представлені результати таких впливів. Розглянуто математичну модель оточення впливів, цільову функцію, обмеження та вирішальне правило для визначення управлінських дій по протидії впливам, що призводять до негативних наслідків в програмах цифровізації. Запропоновано використати математичний апарат теорії несилової взаємодії в якості науково-методичного базису для знаходження оптимального рішення по мінімізації витрат на ліквідацію наслідків негативних впливів. Структура, перелік, підпорядкованість та розподіл зобов’язань в процесі реалізації програм програми цифровізації військової освіти залежать від характерних для динамічного оточення джерел впливів, що призводять до відхилень, і визначають можливість реалізації проєктів цих програм. Оскільки кількість таких джерел у програмах цифровізації значна, необхідно реалізувати системний підхід до побудови систем управління програмами цифровізації військової освіти, який буде ефективним в умовах України. А для цього необхідна розробка методів і способів управління організаційної, функціональної структурою ВНЗ, а також технологіями підготовки, планування, бюджетування, які є в основі побудови систем управління в умовах численних впливів, які виникають в ході реалізації програм цифровізації. Вирішенню цієї наукової задачі і присвячена дана стаття. Тому метою роботи є дослідження впливів динамічного оточення на програми цифровізації вищих навчальних закладів та цифровізації військової освіти, та побудова математичної моделі таких впливів, яка може лягти в основу методології управління впливами на проекти і програми.
НЕГАТИВНІ ВПЛИВИ ДИНАМІЧНОГО ОТОЧЕННЯ НА ПРОГРАМИ ЦИФРОВІЗАЦІЇ ВІЙСЬКОВОЇ ОСВІТИ
Keywords: впливи; проект; програма; інформатизація; негативні впливи; динамічне оточення; управління проєктами; інформаційне середовище; управління впливами; impacts; project; program; informatization; negative impacts; dynamic environment; project management; information environment; impact management